The effects of 2-days repeated competitive stress on saliva immunoglobulin-A responses in trained male athletes - Laing, S.; Jackson, A. R.; Djedovic, N.; Cardinale, M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
A decrease in the salivary concentration of immunoglobulin A (IgA) has been implicated as a possible causal factor in the increased susceptibility of athletes to upper respiratory tract infections (URTI). The aim of this investigation was to determine the effects of two days of competitive biathlon roller-ski racing upon s-IgA concentration and secretion rate, and salivary cortisol and testosterone concentrations. Five male athletes (mean ± SEM; age 25 ± 1 years; height 177 ± 2 cm; body mass 74 ± 2 kg; body fat 10 ± 1 %; VO2max 59 ± 2 ml.kg-1.min-1) volunteered to participate in this study. All athletes were members of the British national team. None of the athletes was taking medications and/or reported symptoms of infections in the 4 weeks prior to the study . On two consecutive days separated by 20 hours, athletes completed 2 biathlon roller ski races consisting or roller skiing and rifle shooting. Race 1 was a 9.3 km SPRINT race characterised by 3 x 3.1 km roller ski loops on an undulating course with 2 x rifle shooting (one lying in a prone position and one from a standing position). Race 2 was a 13 km PURSUIT race characterised by 5 x 2.6 km roller ski loops on an undulating course with 4 x rifle shooting (two lying in a prone position and two from a standing position). During rifle shooting athletes were required to hit five targets positioned at a distance of 50 meters. For every target missed athletes were required to complete a 200 meter penalty loop. Unstimulated whole saliva samples were collected pre- and post- SPRINT and PURSUIT races. Saliva was collected for 3 ± 0.25 minutes by the athlete leaning forward and passively drooling into pre-weighed polypropylene tubes with minimal orofacial movements The s-IgA, cortisol and testosterone concentrations were determined using sandwich-type ELISAs. Saliva IgA secretion rate was determined by multiplying the s-IgA concentration by saliva flow rate. Saliva flow rate increased post-SPRINT (P < 0.01) and post-PURSUIT (P < 0.05) races. Saliva IgA concentration decreased by 53 % following the SPRINT race (P <0.05) and 47 % following the PURSUIT race. Saliva IgA secretion rate showed a trend to increase following both races however was not significant. Salivary cortisol concentration increased post-SPRINT and post-PURSUIT (P < 0.01) races whereas, salivary testosterone decreased post-SPRINT (P < 0.01) and increased post-PURSUIT race (P < 0.05). There was a strong correlation between salivary cortisol concentration and the percentage race time spent between 90-100 % HRmax (R2 0.71, P < 0.01) in the SPRINT race, and there was also a strong correlation between salivary cortisol concentration and the percentage race time spent between 80-89 % HRmax (R2 0.65, P < 0.05) in the PURSUIT race. These findings suggest that athletes undertaking repeated intensive competitions over consecutive days do not demonstrate a reduction in saliva flow rate or s-IgA secretion rate., Sympathetic stimulation does not appear to inhibit saliva flow rate and s-IgA output (secretion rate) shortly after the race.